Application of the Goal Directed Design Framework in the Personality Determination System of Dynamics University Students Based on MBTI Theory Results - Adzkar, Qowiyyu; Wulandari, Sri Hariani Eko; Rahmawati, Endra (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Dinamika University is one of the IT and Business-based campuses located in the city of Surabaya. Dinamika University has 8 departments totaling 1,409 students. Students have experienced stress when facing problems that cannot be solved independently. Solving problems for students also cannot be done instantly, it is necessary to understand yourself in the phase of change that will be passed, which phase also indirectly affects each individual with different stress levels. In addition, these student characteristics are also relevant in measuring learning motivation and learning independence. The solution given is to create a student personality determination system using the MBTI to help identify personality types and to use the Goal Directed Design method to design a system based on user goals. The results of the usability testing evaluation show that the user has successfully completed the given task, and the results of the questionnaire based on the System Usability Scale get an average final score of 80 which is included in the grade A- category, which means that the user assesses the system as good (adjective) and acceptable. (acceptable) and users will recommend this system to others because users already have knowledge and experience in using technology (Net Promoter Score).